2016
DOI: 10.1002/path.4767
|View full text |Cite
|
Sign up to set email alerts
|

Serine-arginine protein kinase 1 promotes a cancer stem cell-like phenotype through activation of Wnt/β-catenin signalling in NSCLC

Abstract: Cancer stem cells (CSCs) are commonly associated with cancer recurrence and metastasis that occurs in up to 30-55% of non-small-cell lung carcinoma (NSCLC) patients. Herein, we showed that serine-arginine protein kinase 1 (SRPK1) was highly expressed at both the mRNA and the protein levels in human NCSLC. SRPK1 was associated with the clinical features of human NSCLC, including clinical stage (p < 0.001) and T (p = 0.001), N (p = 0.007), and M (p = 0.001) classifications. Ectopic overexpression of SRPK1 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 48 publications
0
54
0
2
Order By: Relevance
“…Approach Followed (Testing on Histology Samples/Blood; Data Mining) Level Tested (mRNA; Protein) Clinical Significance Reference Lung data mining; histology samples mRNA; protein ↑SRPK1 was found in NSCLC and was associated with higher tumor stage and shorter survival [29] histology samples mRNA; protein ↑SRPK1 was found in NSCLC [30] data mining mRNA ↑SRPK1 was found in lung adenocarcinoma (a NSCLC histologic type) [31] Breast histology samples mRNA; protein ↑SRPK1 was found in breast cancer and was associated with higher tumor stage and shorter survival [32] histology samples; data mining mRNA; protein ↑SRPK1 was associated with shorter survival in breast cancer and metastatic disease to the lungs and brain [33] data mining mRNA ↑SRPK1 was associated with shorter survival in HER2-negative breast cancer patients treated with chemotherapy [34] histology samples protein ↑SRPK1 was found in breast cancer [35] histology samples protein ↑SRPK1 was found in breast cancer [22] histology samples protein ↑SRPK1 was found in breast cancer and was associated with higher tumor grade [36] Prostate histology samples protein ↑SRPK1 was found in prostate cancer and its precursor (PIN) [26] histology samples protein ↑SRPK1 was found in prostate cancer and was associated with higher stage [37] Colorectal histology samples protein ↑SRPK1 was found in colon cancer and its precursor (adenoma) [22] histology samples protein ↑SRPK1 was found in colon cancer and was associated with higher tumor grade [36] histology samples mRNA; protein ↑SRPK1 was found in colorectal cancer and was associated with higher tumor stage and shorter survival [38] histology samples mRNA; protein ↑SRPK1 was found in colorectal cancer and was associated with higher tumor stage and shorter survival [39] histology samples mRNA ↑SRPK1 was found in colorectal cancer and its precursor (adenoma) [31] histology samples protein ↑SRPK1 and p-AKT were found in colon cancer [40] Stomach data mining mRNA ↑SRPK1 was found in gastric cancer [31] histology samples protein ↑SRPK1 was found in gastric cancer and was associated with higher tumor stage and shorter survival [41] histology samples protein ↑SRPK1 was found in gastric cancer [42] histology samples mRNA; protein ↑SRPK1 was found in gastric cancer and was associated with higher tumor stage and shorter survival [43] Liver histology samples mRNA; protein ↑SRPK1 was associated with higher stage and shorter survival; SRPK1 expression was inversely correlated with miR-1296 expression…”
Section: Cancer Type (Primary Location)mentioning
confidence: 99%
“…Approach Followed (Testing on Histology Samples/Blood; Data Mining) Level Tested (mRNA; Protein) Clinical Significance Reference Lung data mining; histology samples mRNA; protein ↑SRPK1 was found in NSCLC and was associated with higher tumor stage and shorter survival [29] histology samples mRNA; protein ↑SRPK1 was found in NSCLC [30] data mining mRNA ↑SRPK1 was found in lung adenocarcinoma (a NSCLC histologic type) [31] Breast histology samples mRNA; protein ↑SRPK1 was found in breast cancer and was associated with higher tumor stage and shorter survival [32] histology samples; data mining mRNA; protein ↑SRPK1 was associated with shorter survival in breast cancer and metastatic disease to the lungs and brain [33] data mining mRNA ↑SRPK1 was associated with shorter survival in HER2-negative breast cancer patients treated with chemotherapy [34] histology samples protein ↑SRPK1 was found in breast cancer [35] histology samples protein ↑SRPK1 was found in breast cancer [22] histology samples protein ↑SRPK1 was found in breast cancer and was associated with higher tumor grade [36] Prostate histology samples protein ↑SRPK1 was found in prostate cancer and its precursor (PIN) [26] histology samples protein ↑SRPK1 was found in prostate cancer and was associated with higher stage [37] Colorectal histology samples protein ↑SRPK1 was found in colon cancer and its precursor (adenoma) [22] histology samples protein ↑SRPK1 was found in colon cancer and was associated with higher tumor grade [36] histology samples mRNA; protein ↑SRPK1 was found in colorectal cancer and was associated with higher tumor stage and shorter survival [38] histology samples mRNA; protein ↑SRPK1 was found in colorectal cancer and was associated with higher tumor stage and shorter survival [39] histology samples mRNA ↑SRPK1 was found in colorectal cancer and its precursor (adenoma) [31] histology samples protein ↑SRPK1 and p-AKT were found in colon cancer [40] Stomach data mining mRNA ↑SRPK1 was found in gastric cancer [31] histology samples protein ↑SRPK1 was found in gastric cancer and was associated with higher tumor stage and shorter survival [41] histology samples protein ↑SRPK1 was found in gastric cancer [42] histology samples mRNA; protein ↑SRPK1 was found in gastric cancer and was associated with higher tumor stage and shorter survival [43] Liver histology samples mRNA; protein ↑SRPK1 was associated with higher stage and shorter survival; SRPK1 expression was inversely correlated with miR-1296 expression…”
Section: Cancer Type (Primary Location)mentioning
confidence: 99%
“…For example, the splicing factor serine-arginine protein kinase 1 (SRPK1) has been reported to stimulate a stem cell-like phenotype in human NSCLC [12] . Gong et al found that SRPK-transduced cells expressed higher levels of pluripotency-associated markers and greater self-renewal capacity [12] . Further they performed gene knockdown experiment to suppress expression of SRPK and demonstrated the converse effect.…”
Section: Research Highlightmentioning
confidence: 99%
“…These events could explain rapid tumor relapse and a poor prognosis in cancer patients . Several signaling pathways, such as Sonic Hedgehog, Wnt/β‐catenin, EGFR and SOX2, have been described to regulate the behavior of CSCs and EMT, and contribute to the development of several cancers, such as lung cancer …”
Section: Introductionmentioning
confidence: 99%
“…6 These events could explain rapid tumor relapse and a poor prognosis in cancer patients. 7,8 Several signaling pathways, such as Sonic Hedgehog, 9 Wnt/β-catenin, 10 EGFR 11 and SOX2, 12 have been described to regulate the behavior of CSCs and EMT, and contribute to the development of several cancers, such as lung cancer. 9 EGFR is a receptor tyrosine kinase (RTK) that is stimulated by its ligands such as EGF, amphiregulin, betacellulin, epiregulin, neuregulin, heparin-binding EGF, and transforming growth factor alpha (TGF-α).…”
Section: Introductionmentioning
confidence: 99%